The Linguistic Turn and Deliberative Development of Public Administration - Mendoza-Dreisbach, Sharon; Dreisbach, Jeconiah (Journal of Public Administration and Government, 2025)
This article examines the paradigmatic shift known as the linguistic turn within the field of public administration, exploring its profound implications for both theory and practice. Originating from philosophical discourse, the linguistic turn challenges traditional positivist approaches by foregrounding language and discourse as central to understanding administrative processes and outcomes. Through a comprehensive review of literature, this paper elucidates how this theoretical shift has reshaped the landscape of public administration. The study investigates the history and impact of linguistic theories on administrative practices, highlighting the emergence of discursive strategies in policy formulation, implementation, and evaluation. It critically analyzes how language constructs realities, shapes bureaucratic interactions, and influences policy effectiveness. Moreover, the deliberative development reveals how policy issues are framed through narratives and metaphors, influencing policy outcomes, highlights the importance of inclusive and rational deliberation in democratic legitimacy, advocating for participatory decision-making processes, and addresses the practical challenges of implementing inclusive deliberation in diverse societies, emphasizing accessibility and respectful dialogue. By integrating insights from linguistics, philosophy, and public administration, it argues for a more nuanced approach that acknowledges the linguistic dimensions of governance, promoting participatory, transparent, and equitable policy-making. The article suggests avenues for future research and practical implications for enhancing administrative effectiveness in diverse socio-political contexts.